If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 = -3x + 5 Reorder the terms: -4 + 6x = -3x + 5 Reorder the terms: -4 + 6x = 5 + -3x Solving -4 + 6x = 5 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + 6x + 3x = 5 + -3x + 3x Combine like terms: 6x + 3x = 9x -4 + 9x = 5 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 9x = 5 + 0 -4 + 9x = 5 Add '4' to each side of the equation. -4 + 4 + 9x = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 5 + 4 9x = 5 + 4 Combine like terms: 5 + 4 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 13y-3=53-y | | 4p+5q=60y | | a/6=-9 | | 5x^2-24x=-28 | | 7x+14=9x+2 | | x^2-12xy+20y^2= | | 4-3y=29 | | 4/21+8/21= | | 3*f-12=3(f-12) | | (5-5i)(5+5i)=0 | | .644-28.98x+318x^2=0 | | 6(x-3)=-6x+90 | | 6(x-3)=6x+90 | | P+14=34 | | 5-(x+3)=12 | | K*8+42-18+E*15=X | | 4*d-5=-d | | 2x-6+5x=8 | | 2-5*h+3=-28 | | X+7=3+4 | | 2x-7+4=11 | | 11x=77 | | X^2+14x+55=0 | | 4(-2)z+8(-2)+3+(-2)+6= | | 4x+3-2x=28 | | 18=6t | | 14-3x=47 | | -2x+-6+1=-7 | | 5-7x=-16 | | 5x+41=105-3x | | 4u^2-28u-72= | | 591x=3 |